PENGARUH CAPITAL INTENSITY, LEVERAGE, LIKUIDITAS, TAX TO BOOK RATIO DAN RISIKO BISNIS TERHADAP KINERJA KEUANGAN - Fandina Isticha Noor, Fandina (Media Mahardhika, 2024)
This research aims to test whether capital intensity, leverage, liquidity, tax to book ratio and business risk have an effect on financial performance (empirical study of property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2022 period). This data uses secondary data. The sample for this research is property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2019-2020 using the purposive sampling method. There are 72 companies that meet the criteria as research samples. This research uses quantitative methods. This research uses quantitative methods. The variables used are capital intensity, leverage, liquidity, tax to book ratio, business risk and financial performance. The test used is multiple linear regression analysis using the SPSS 27 program application. The results of this research show that the variables capital intensity, leverage, liquidity have a significant effect on financial performance, and tax to book ratio, business risk has a significant effect on financial performance.